POST-WAR EVERYDAY LIFE AND TRAUMATIC CONSCIOUSNESS IN “MRS DALLOWAY”: A LINGUO-PRAGMATIC AND COGNITIVE ANALYSIS (SCIENCE TIME JOURNAL, 2026)
This article investigates the representation of post-war everyday life and traumatic consciousness in Virginia Woolf’s Mrs Dalloway through an interdisciplinary framework combining trauma narratology, cognitive poetics, and linguo-pragmatic analysis. The study examines how the novel reflects the psychological aftermath of World War I through fragmented narration, temporal dislocation, symbolic discourse, and internal monologue. Drawing upon the theoretical perspectives of Mikhail Bakhtin, Roman Jakobson, and John Searle, the research analyses the dialogic structure of consciousness, the poetic function of traumatic discourse, and the pragmatic implications of silence and speech acts. The study employs linguistic, semantic, and pragmatic methodologies to explore trauma representation in both individual and collective dimensions. Special attention is paid to ethnonymic and socio-cultural markers functioning as identity constructs within post-war British discourse. The findings reveal that Woolf constructs traumatic consciousness through syntactic fragmentation, metaphorical encoding, disrupted temporality, and polyphonic narration.